Literature Review: Solar Energy for Alternative Renewable Energy and Potential Application in Indonesia - Andi Sulistiyono; Hamdi Rifai; Nofi Yendri Sudiar (Institute for Research and Community Service (LPPM), Universitas Malikussaleh, Indonesia, 2025)
Electrical energy has become a human need along with economic improvements and technological advances that require an unlimited supply of energy. Its nature is limited to fossil energy sources and also causes environmental pollution, so it is necessary to use renewable energy as another energy source to overcome this problem. Solar energy is freely available, is an environmentally friendly energy source whose application results have been proven and have promising prospects for the future. This paper presents the results of a research review on the use of solar energy as an alternative source of renewable energy, the basic concept of obtaining it and some results of using this energy. Next, we will briefly review the potential and use of solar energy sources in Indonesia. The high potential of solar energy in Indonesia needs to be processed and regulations that support the development of solar energy power plants as an alternative energy. Technically, solar photovoltaic energy has the potential to become an alternative energy source for the masses in the future as a substitute for fossil energy and to meet the electrical energy needs of remote areas.